(untitled) (Materiali di Estetica. Terza serie, 2019)
The article is a report of the comparative aesthetics seminar held in 2018 at the Rimini’s School of Oriental and Comparative Philosophy. Various and interesting topics related to intercultural aesthetics were discussed: the philosophical ideas underlying Chanoyu; the link between culture, perception, representation and language; the history of the reception of non-European works in Western culture; characteristic aspects of Buddhist, Chinese and Japanese art.